The civil wars of Julia Ward Howe a biography - Showalter, Elaine 1941- (Simon & Schuster, 2016)
"Julia Howe (1819 -1910) was a beautiful, studious New York heiress and aspiring poet when she married Bostonian Dr. Samuel Gridley Howe, a hero of the Greek war of independence against the Turks and an internationally acclaimed pioneer in the education of the blind. Their marriage united two exceptional people. Together the Howes knew many of the key figures of their era, from Charles Dickens and Florence Nightingale in England, to Margaret Fuller, Henry Wadsworth Longfellow, Horace Mann, Charles Sumner, and John Brown. But despite his philanthropic and abolitionist ideals, Dr. Howe did not support married women's work outside the home. He isolated Julia, opposed her literary ambitions, and wasted her inheritance. She defied him by continuing to publish poems and plays while raising their six children. She also secretly wrote a bold novel about a hermaphrodite, undiscovered until long after her death. And during the Civil War, she wrote the words to the most powerful and enduring anthem in the nation's history. Authorship of the 'Battle Hymn of the Republic' made her famous and revered. But she fought her own civil war at home, battling with her husband over her rights to equality, intellectual freedom, and a public voice. As soon as the war ended, she became a pacifist and suffragist leader. In the second half of her life, she came into her own as a tireless campaigner for women's rights and social reform. In this biography, Elaine Showalter tells the story of Howe's determined self-creation and vividly restores her to the pantheon of feminist intellectuals who changed the world."--Dust jacket
Includes bibliographical references (page 249-[278]) and index
Keywords: Howe, Julia Ward / 1819-1910; Howe, Julia Ward -- 1819-1910; American Civil War (1861-1865); Geschichte 1800-1900; Authors, American / 19th century / Biography; Feminists / United States / Biography; Authors, American; Feminists; Women; Frau; Geschichte; Sezessionskrieg (1861-1865); Frauenwahlrecht; Feministin; United States / History / Civil War, 1861-1865 / Women; United States; USA; Biografie